PROFESSIONAL SELF-DETERMINATION OF SENIOR SCHOOLCHILDREN IN ENGINEERING AND TECHNICAL EDUCATIONAL ENVIRONMENT - Elena P. Chubova; Vera V. Boguslavskaya (Advanced Engineering Research, 2011)
Actual engineering education content, problems of professional self-determination of the senior schoolchildren in the field of engineering and technical education are considered. Factors affecting the choice of engineering trades by senior schoolchildren are analyzed.